1996
DOI: 10.1128/iai.64.10.4078-4084.1996
|View full text |Cite
|
Sign up to set email alerts
|

Pertussis-specific cell-mediated immunity in infants after vaccination with a tricomponent acellular pertussis vaccine

Abstract: The aim of this study was to investigate pertussis-specific cell-mediated immunity in infants vaccinated with a tricomponent acellular vaccine. Infants were investigated during a primary vaccination schedule from the third month of life to the sixth month as well as before and after a booster at 15 to 24 months. This is the first report of specific cell-mediated immune responses to pertussis-related antigens in infants below the age of 12 months. Our data show that the vaccine induces T-cell responses specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(26 citation statements)
references
References 49 publications
1
24
0
1
Order By: Relevance
“…Despite recent experimental and clinical investigations of induction and expression of immune responses against Bordetella pertussis, the mechanisms underlying protection from pertussis are not completely understood (8,15,25). Although data from experimental infections suggest that both T and B memory cell compartments are involved (18,20,23,26), it is not clear which component(s) of adaptive immune responses mediates protection induced by vaccination in infants and to what extent the mechanisms of protection induced by whole-cell pertussis (wP) or acellular pertussis (aP) vaccines differ from each other (4,7,13,29,36). Conflicting information has been generated about the existence of serologic correlates of protection (1,9,10,21,22,32,33).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite recent experimental and clinical investigations of induction and expression of immune responses against Bordetella pertussis, the mechanisms underlying protection from pertussis are not completely understood (8,15,25). Although data from experimental infections suggest that both T and B memory cell compartments are involved (18,20,23,26), it is not clear which component(s) of adaptive immune responses mediates protection induced by vaccination in infants and to what extent the mechanisms of protection induced by whole-cell pertussis (wP) or acellular pertussis (aP) vaccines differ from each other (4,7,13,29,36). Conflicting information has been generated about the existence of serologic correlates of protection (1,9,10,21,22,32,33).…”
mentioning
confidence: 99%
“…We have recently addressed the study of cell-mediated immunity (CMI) against B. pertussis antigens in children participating in the Italian Efficacy Trial of wP and aP vaccines (12). We have shown that CMI persisted in these children up to 20 months of age (4,7,29,36), and a correlation between clinical efficacy and percentage of vaccinees acquiring CMI to pertussis toxin (PT) was apparent (7). Coupled with evidence from experimental models of infection (18,23,26), the above-mentioned studies suggested that CMI induction could play a role in protection induced by vaccination and in its persistence despite the early fall of antibody (Ab) levels (4,7,11,13,29,36).…”
mentioning
confidence: 99%
“…In a recent study (34), Ryan et al demonstrated a preferential induction of T-helper 1 (Th1) cells in preschool children with B. pertussis infection. Zepp et al reported that primary immunization with a tricomponent acellular pertussis vaccine induced predominantly Th1 cells in infants (41). In contrast, Ausiello et al, also by vaccinating infants, found that an acellular vaccine induced cytokines of both types, whereas a whole-cell vaccine induced cytokines of Th1 type (2).…”
mentioning
confidence: 99%
“…Für das immunologische Gedächtnis ist weiterhin die T-Zell-vermittelte Immunität von großer Bedeutung. Es konnte außerdem gezeigt werden, dass bei einer Impfung mit einem azellulären Keuchhustenimpfstoff die T-Zell-vermittelte Immunität nach der Grundimmunisierung bis zur Boosterimpfung hin persistiert, wohingegen Antikörper im Serum schon lange nicht mehr nachweisbar waren, obwohl klinisch ein Schutz vor Pertussis bestand (39).…”
Section: Vaccinations Of Preterm Infantsunclassified